2020
DOI: 10.1177/2048872620901835
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of pleural effusions on thoracic ultrasound in acute heart failure

Abstract: Background: Although pleural effusions are common among patients with acute heart failure, the relevance of pleural effusion size assessed on thoracic ultrasound has not been investigated systematically. Methods: In this prospective observational study, we included patients hospitalised for acute heart failure and performed a thoracic ultrasound early after admission (thoracic ultrasound 1) and at discharge (thoracic ultrasound 2) independently of routine clinical management. A semiquantitative score was appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 24 publications
0
32
0
Order By: Relevance
“…In 2012, a council of experts recommended the use of the 8-zone protocol for the assessment of interstitial syndrome. 16 Our study has some limitations. There were a small number of studies meeting inclusion criteria, and the studies found were heterogeneous in terms of the study period, the number of zones visualized, the cut-off point of B lines, the scales used, and the follow-up time.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…In 2012, a council of experts recommended the use of the 8-zone protocol for the assessment of interstitial syndrome. 16 Our study has some limitations. There were a small number of studies meeting inclusion criteria, and the studies found were heterogeneous in terms of the study period, the number of zones visualized, the cut-off point of B lines, the scales used, and the follow-up time.…”
Section: Discussionmentioning
confidence: 89%
“…High pre-discharge lung ultrasound pleural effusion scale scores (47% residual effusion present) were not associated with increased readmission or death at 90 days (adjusted HR 10 5.95% CI 0.92-1.19; p = 046) while a finding of ≥7 B-lines at discharge was independently associated (adjusted HR 2.43, 95% CI 1.11-5.37; p = 0.027). 16…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pleural effusions (PEs) scoring method: A semiquantitative score from 0 to 4 points was assigned for each hemithorax and 0 to 8 for both thoraces; thus, the total PEs scores were 0 to 8 for each patient [ 15 ] (Fig. 3 ) (Additional files 1–5: Videos 1–5).…”
Section: Methodsmentioning
confidence: 99%
“…If clinically indicated, patients underwent an upright CXR examination on admission. These CXRs were analysed by radiologists for the presence of vascular congestion, interstitial oedema, and alveolar oedema 5 . Only CXR examinations performed within 1 day of admission based on date change were included in this analysis.…”
Section: Methodsmentioning
confidence: 99%